(3TQM bUjOI CHh GdaJMs - (3GdMSjfj GdfjSGHhQqi, GdTQja (B, (3LeGd GdOjf (B, (3GdfbQg cGQ, YHO Gddg Hf eMeO Hf CMeO, (B776 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd edM GdYdhe Yde GdYQHjI (B... (3aEfj deG CdbGfj GdJbOjQ GdEdgj (B... (3Ke GdJeSh efj Cf CTQM GdbUjOI GdefShHI Edi efTF GddWGFa hGdObGFb CHj GdaJM GdHSJj TQMG jQaY SfGHQgG (B...s
(3BNQgG (B:s
(3dCf CdaGXgG aj GdSdGSI CLQi ef GdeGA heYGfjgG CMdi ef GdYSd hEf de jcf UGFZgG eNJGQ GdTYQGA aMGdG Hjf GdaVdGA GdMSGf QVj Gddg Yfg YfO MGUdg Cfg dG JYJHQ GdTYQ (B...(3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\126s
(3cTa GdXfhf (B2\1336s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs